Recent advances of nanotechnology in COVID 19: A critical review and future perspective - Kabi Raj Chaudhary; Sima Kujur; Karanvir Singh (Elsevier, 2023)
The global anxiety and economic crisis causes the deadly pandemic coronavirus disease of 2019 (COVID 19) affect millions of people right now. Subsequently, this life threatened viral disease is caused due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, morbidity and mortality of infected patients are due to cytokines storm syndrome associated with lung injury and multiorgan failure caused by COVID 19. Thereafter, several methodological advances have been approved by WHO and US-FDA for the detection, diagnosis and control of this wide spreadable communicable disease but still facing multi-challenges to control. Herein, we majorly emphasize the current trends and future perspectives of nano-medicinal based approaches for the delivery of anti-COVID 19 therapeutic moieties. Interestingly, Nanoparticles (NPs) loaded with drug molecules or vaccines resemble morphological features of SARS-CoV-2 in their size (60-140 nm) and shape (circular or spherical) that particularly mimics the virus facilitating strong interaction between them. Indeed, the delivery of anti-COVID 19 cargos via a nanoparticle such as Lipidic nanoparticles, Polymeric nanoparticles, Metallic nanoparticles, and Multi-functionalized nanoparticles to overcome the drawbacks of conventional approaches, specifying the site-specific targeting with reduced drug loading and toxicities, exhibit their immense potential. Additionally, nano-technological based drug delivery with their peculiar characteristics of having low immunogenicity, tunable drug release, multidrug delivery, higher selectivity and specificity, higher efficacy and tolerability switch on the novel pathway for the prevention and treatment of COVID 19.